Optimal Portfolio Construction: Application of Sharpe's Single-Index Model on Dhaka Stock Exchange - Mahmud, Imroz (University of Islam Malang, 2019)
This study aims to find whether Sharpe's single-index model of portfolio construction offers better investment alternatives to the investors of the Dhaka Stock Exchange (DSE). For this purpose, month-ended closing price data of 178 companies listed on the DSE, the prime bourse of Bangladesh, and the month-ended index value of DSEX have been used for the period starting from January 2013 to February 2018. The stocks selected for this study belong to 16 industrial sectors, and purposive sampling technique has been used to select these sectors. Sharpe's model formulates a unique cut-off rate and selects the stocks having an excess return-to-beta ratio above that rate. In this study, 54 stocks qualified to be a part of the optimal portfolio. Hence, the proportion of investment to be made on each of the stock is calculated according to the model. The study reveals that three industries occupy a hefty chunk (65.78%) of the proposed investment portfolio. The constructed portfolio offers a monthly return of 2.1489% and carries 1.9516% risk as measured by standard deviation. The beta of the optimal portfolio is only 0.124003. The constructed portfolio outperforms every individual stock as well as the market index in terms of offering the optimal risk-return combinations. Therefore, this five-and-a-half-decade-old model offers a great opportunity for Bangladeshi investors to optimize return and diversify risk in an efficient manner.